Ketamine and its combination with pentazocine and meperidine for epidural anaesthesia in dogs - RAM, R P; DASS, L L; SHARMA, A K (The Indian Journal of Animal Sciences, 2014)
Clinically healthy dogs (15) of either sex aged about 1 year were randomly grouped into 3 with 5 dogs each to study the effect of epidural administration of ketamine alone and in combination with pentazocine and meperidine on clinic – anaesthetic profile in dogs. Ketamine hydrochloride @3 mg/kg b.wt and ketamine @3mg/kg b.wt in combination with pentazocine lactate @ 0.3 mg/kg b.wt and ketamine @ 3mg/kg b.wt in combination with meperidine @ 1mg/kg b.wt were administered epidurally in animals of group 1, 2 and 3, respectively. Marked alteration in rectal temperature, heart rate and respiration rate were recorded at initial intervals of observations in all the groups, however, these values returned towards normalcy by the end of 120 min of observation. Quicker onset of analgesia was recorded in group 2 (3.68±0.22 min) followed by group 3 (3.88±0.17 min) and group 1 (4.08±0.33 min). The duration of analgesia, standing time and recovery time were significantly longer in group 2 and 3 as compared to group 1. None of the groups showed significant variation in duration of recumbency. The treated animals manifested minimum, transient and occasional untoward reactions. It is concluded that pentazocine and meperidine can be given epidurally in combination with ketamine for effective analgesia in dogs.